Platelet-Derived NO in Subjects Affected by Type 2 Diabetes with and without Complications: Is there any Relationship with their Offspring? - Sabbatinelli, Jacopo; Vignini, Arianna; Salvolini, Eleonora; Nanetti, Laura; Mazzanti, Laura; Anna Rabini, Rosa (Experimental and Clinical Endocrinology & Diabetes, 2017)
Macro- and microvascular complications are currently the principal causes of morbidity and mortality in patients with diabetes mellitus. Aim of this study was to determine if type 2 diabetic patients with nephropathy and coronary artery disease showed altered platelet-derived nitric oxide (NO) production, compared with diabetic subjects without complications, and if this alteration is also present in their diabetic offspring. In this case-control observational study, platelet NO and peroxynitrite content was determined on plasma from 60 male adult type 2 diabetic patients and 60 male offspring type 2 diabetic patients. Plasmatic levels of homocysteine were also determined in the same individuals. Moreover, Western blot analysis of platelet lysates was performed with specific monoclonal antibody for endothelial (eNOS) and inducible (iNOS) nitric oxide synthase. Our study showed a lower piastrinic production of NO in the group of parents without complications (ADH), compared with the group of offspring without complications (YDH) and with the groups of parents with complications. Furthermore, we observed a lower synthesis of peroxynitrite in platelets from the ADH group than in the groups of patients with complications, and in the YDH group compared with all other groups. Subjects from YDH group also showed lower iNOS expression, compared with all other groups. Our data suggest that alterations in nitric oxide metabolism may represent potential risk factors in type 2 diabetes complications, such as nephropathy and cardiovascular diseases, leading to development of new therapeutic strategies in order to delay and prevent the onset of such complications.
Keywords: coronary artery disease; diabetic nephropathy; oxidative stress; peroxynitrite